Participatory Budgeting: Action Research Procedures in Community Work - Mandrysz, Witold (Participatory Social Work: Research, Practice, Education, 2019)
Implementation of actions based on consensus and social dialogue builds a proper climate for cooperation among all social forces in order to solve a given problem or achieve a definite goal, also at local community level (Cohen, 1978; Ross, 1967). One of the manifestations of the practical implementation of the concept of participatory democracy and civil dialogue at the local community level, are actions within assumptions of participatory budgeting which may be defined as a form of “collective” decision-making process, within the framework of which, the inhabitants along with the local authorities co-create the city budget (Ganuza, Baiocchi, 2012; Górski 2007). A specific method that enables the checking of the level of willingness of members of a community to undertake common project actions is a participating intervention research. Planning extensive and costly environmental projects such as revitalization projects, should be preceded with implementation of a participatory budget according to methodology of participating intervention research.